How Frequently Do Consumer Prices Change in Austria? Evidence from Micro CPI Data - Josef Baumgartner; Ernst Glatzer; Fabio Rumler; Alfred Stiglbauer (Oesterreichische Nationalbank (OeNB), 2005)
In this paper a data set with price records collected for the computation of the Austrian CPI is used to estimate the average frequency of price changes and the duration of price spells to provide empirical evidence on the degree and characteristics of price rigidity in Austria. Depending on the estimation method applied, on average, prices are unchanged for 10 to 14 months. We find a strong heterogeneity across sectors and products. Price increases occur only slightly more often than price decreases. For both cases the typical size of the weighted average price change is quite large (11 and 15 percent, respectively). Like in related contributions we find that the aggregate hazard function is decreasing with time. Apart from heterogeneity across products and price setters, this is due to oversampling of products with a high frequency of price changes. Accounting for the unobserved heterogeneity in estimating the probability of a price change with a panel logit model (with fixed elementary product effects), we find a small but positive effect of the duration of a price spell on the probability of a price change. We also find that during the Euro cash changeover period the probability of price changes was higher.
Keywords: C41; D21; E31; L11; 330; Consumer prices; sticky prices; frequency and synchronization of price changes; duration of price spells